Leading Online Professional Development for Instructional Technology Coaches with Effective Design Elements - Janet Cowart; Yi Jin (MDPI AG, 2024)
This single-case study focused on the impact of design elements in online professional development for Instructional Technology Coaches to develop their TPACK. In this study, 30 participants enrolled in an online professional development series of synchronous and asynchronous sessions called Pathways. Ten design elements were implemented including content-focused, active learning, collaboration, modeling, coaching support, feedback, sustained duration and time, reflection, resources, and utilization of technology. Qualitative data were collected from 28 participants' feedback forms, interviews, and asynchronous assignments. The results showed that all ten design elements were perceived to be beneficial to Instructional Technology Coaches' learning. However, at the same time, some participants found a few hindrances to their learning from certain aspects of the six design elements. Hindrances in Pathways' design elements include ineffective modeling, collaboration challenges, off-topic discussions, unfamiliarity with Teams, technical difficulties, insufficient time, and home distractions. These findings emphasize the need for effective collaboration, time allocation, and technical proficiency. The coaches developed their TPACK through Pathways as discovered by the rubric results of the asynchronous assignments. Directions for future research and recommendations for professional development are discussed.